Digital Transformation and Sustainability in Export Financing: A Case Study of The Indonesia Eximbank (LPEI) - Indah Salsa Noviyanti (Jurnal Indonesia Sosial Sains, 2025)
The background of this research is the importance of understanding the role of the Indonesian Export Financing Agency (LPEI) in supporting national economic growth, especially through sustainable and innovative export financing. Digital transformation and the adoption of sustainability (ESG) principles are both challenges and opportunities for LPEI to improve Indonesia's competitiveness in the global market. This study aims to analyze the strategy and implementation of export financing by LPEI, focusing on risk management, the effectiveness of digital transformation, and the adoption of a sustainability framework. The research uses a qualitative descriptive method with data obtained through observation, literature study, and interviews with relevant parties at LPEI. The results show that LPEI has successfully adopted digital technology to improve operational efficiency, such as the use of digital financing platforms and technology-based risk management systems. In addition, the green financing program initiated by LPEI supports environmentally friendly projects, in line with global sustainability trends. However, the research also found challenges such as limited human resources and regulatory barriers in implementing this transformation. The conclusion of this study confirms that LPEI plays a strategic role in supporting Indonesia's export growth, but internal capacity strengthening and cross-sector collaboration are needed to maximize its impact.